Neurocardiovascular coupling in congenital diaphragmatic hernia patients undergoing different types of surgical treatment - Hendrikx, Dries; Costerus, Sophie A.; Zahn, Katrin; Perez Ortiz, Alba; Dorado, Alexander Caicedo; Van Huffel, Sabine; de Graaff, Jurgen; Wijnen, René; Wessel, Lucas; Tibboel, Dick; Naulaers, Gunnar (European journal of anaesthesiology, 2022)
BACKGROUND: The effect of peri-operative management on the neonatal brain is largely unknown. Triggers for perioperative brain injury might be revealed by studying changes in neonatal physiology peri-operatively. OBJECTIVE: To study neonatal pathophysiology and cerebral blood flow regulation peri-operatively using the neuro-cardiovascular graph. DESIGN: Observational, prospective cohort study on perioperative neuromonitoring. Neonates were included between July 2018 and April 2020. SETTING: Multicentre study in two high-volume tertiary university hospitals. PATIENTS: Neonates with congenital diaphragmatic hernia were eligible if they received surgical treatment within the first 28 days of life. Exclusion criteria were major cardiac or chromosomal anomalies, or syndromes associated with altered cerebral perfusion or major neurodevelopmental impairment. The neonates were stratified into different groups by type of peri-operative management. INTERVENTION: Each patient was monitored using near-infrared spectroscopy and EEG in addition to the routine peri-operative monitoring. Neurocardiovascular graphs were computed off-line. MAIN OUTCOME MEASURES: The primary endpoint was the difference in neurocardiovascular graph connectivity in the groups over time. RESULTS: Thirty-six patients were included. The intraoperative graph connectivity decreased in all patients operated upon in the operation room (OR) with sevoflurane-based anaesthesia (P < 0.001) but remained stable in all patients operated upon in the neonatal intensive care unit (NICU) with midazolam-based anaesthesia. Thoracoscopic surgery in the OR was associated with the largest median connectivity reduction (0.33 to 0.12, P < 0.001) and a loss of baroreflex and neurovascular coupling. During open surgery in the OR, all regulation mechanisms remained intact. Open surgery in the NICU was associated with the highest neurovascular coupling values. CONCLUSION: Neurocardiovascular graphs provided more insight into the effect of the peri-operative management on the pathophysiology of neonates undergoing surgery. The neonate's clinical condition as well as the surgical and the anaesthesiological approach affected the neonatal physiology and CBF regulation mechanisms at different levels. TRIAL REGISTRATION: NL6972, URL: https://www.trialre-gister.nl/trial/6972.